2022
DOI: 10.1002/slct.202202263
|View full text |Cite
|
Sign up to set email alerts
|

Novel Derivatives of 4,6‐Dihydroxy‐2‐Quinolone‐3‐Carboxamides as Potential PI3Kα Inhibitors

Abstract: The phosphatidylinositol 3‐kinase/protein kinase B (PI3K/AKT) pathway is a crucial pathway in cancer pathogenesis. Novel derivatives of 4,6‐dihydroxy‐2‐quinolone‐3‐carboxamides were synthesized as potential PI3Kα inhibitors. Derivatives’ chemical identity was approved using 1H‐NMR, 13C‐NMR, FTIR, and MS. Cytotoxicity was evaluated on the breast (MCF‐7) and colon cancer (HCT‐116) cell lines using the CCK8 assay. Apoptosis was assessed by Annexin‐PI staining. Western blotting was employed to assess the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Results demonstrated that two N-phenyl-6-chloro carboxamide analogues (q6, q7; Figure 3) exerted significant toxicity against human epithelial colorectal adenocarcinoma (Caco-2) and human colon cancer (HCT-116) cell lines. Furthermore, two 4,6-dihydroxy-2-quinolone-3-carboxamide derivatives (q8, q9; Figure 3) exhibited the most potent cytotoxic effect on breast cancer (MCF-7) and colon cancer (HCT-116) cell lines [39,40]. In 2020, Srigouri Huddara and his team introduced 4-hydroxy-2-oxo-1,2-dihydroquinolines as potential inhibitors of Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that two N-phenyl-6-chloro carboxamide analogues (q6, q7; Figure 3) exerted significant toxicity against human epithelial colorectal adenocarcinoma (Caco-2) and human colon cancer (HCT-116) cell lines. Furthermore, two 4,6-dihydroxy-2-quinolone-3-carboxamide derivatives (q8, q9; Figure 3) exhibited the most potent cytotoxic effect on breast cancer (MCF-7) and colon cancer (HCT-116) cell lines [39,40]. In 2020, Srigouri Huddara and his team introduced 4-hydroxy-2-oxo-1,2-dihydroquinolines as potential inhibitors of Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%